Government crisis communication innovation and its psychological intervention coupling: Based on an analysis of China’s provincial COVID-19 outbreak updates - Zhou, Shen; Yu, Wensheng; Tang, Xinwen; Li, Xiaoqian (Frontiers in Psychology, 2023)
Outbreak updates are an integral part of the crisis communication of epidemics. In the crisis communication of Covid-19, localities in China present different characteristics in managing outbreak updates, which largely determine the effect of crisis communication and the evolution of social psychology. Depending on the analysis of the texts of the updates in 31 provincial (autonomous regions and municipalities directly under the central government) health committees in China, the study finds the differences in provincial outbreak updates and summarizes 12 innovative crisis communication ways. A coupling analysis was applied using the equilibrium-cognitive-psychosocial transition model to further expound on the psychological connotation and intervention potential of the crisis communication innovations. The coupling of crisis communication with interventions has a positive effect on the formation of crisis communication strategies that take psychological factors into account. It can help construct and optimize the public crisis communication system and put "care" in the middle of the modernization of emergency management capacity.